FILSAFAT PENDIDIKAN ANAK USIA DINI PERSPEKTIF AL-GHAZALI - Helmy Hidayatulloh; Ahmad Hidayat; Kosasih Kosasih; Hasanudin Hasanudin; Nurkhairina Nurkhairina (Staisman Press, 2024)
This research aims to examine the concept of early childhood education based on Al-Ghazali's thinking, which emphasizes moral and religious development as the main goal of education, with a focus on moral formation and soul purification to get closer to Allah (taqarrub ilallah). The problem formulated in this research includes the relevance of Al-Ghazali's thoughts to early childhood education, especially in the context of Islamic values ​​originating from the Al-Qur'an and As-Sunnah. The research method used is a qualitative approach with a descriptive-analysis method based on literature study, which utilizes primary literary sources such as the book Ihya Ulumuddin and other works of Al-Ghazali. Data was analyzed using content analysis techniques to explore deep meanings related to educational concepts. The results of the research show that Al-Ghazali views education as a means to develop the physical and spiritual potential of children born in a fitrah state. Moral-spiritual education is the main foundation, supported by balanced physical, intellectual and social development. Al-Ghazali emphasized the importance of the role of parents, the use of learning methods based on the child's developmental stage, and the balance between example and instruction. Al-Ghazali's thoughts are relevant to modern education, which aims to form individuals who are faithful, devout and capable of facing life, both worldly and spiritual.